The self‐concept of person with chronic schizophrenia in Japan. Issue 3 (29th June 2018) - Sugawara, Hiromi; Mori, Chizuru
Abstract: Aims: People with schizophrenia have some problems in terms of function of consciousness of the self. Therefore, what they are conscious of themselves remains unclear. The aim of this study was to elucidate the self‐concept of Japanese with schizophrenia. Methods: We interviewed Japanese with a diagnosis of schizophrenia and analyzed the interview transcription by means of qualitative content analysis. Results: Qualitative content analysis yielded 2001 meaning units and 53 codes from the transcription. The codes were classified into 6 categories: Present Cognition and Definition of the Self, Feeling Towards and Evaluation of the Self, The Self That Is Seen by Others, The Past Self‐Image, The Self‐Image About Possibility and the Future, and How I Should Be and the Ideal Self . Conclusion: One of the categories, Feeling Towards and Evaluation of the Self, means self‐confidence, pride, and self‐acceptance. In this category, some participants could not accept themselves because they felt "this is not the true self." Considering our finding and the background in Japan, psychiatric hospitalization is long, while hospitalized people with schizophrenia might be aware of the negative stereotypes about them. Therefore, staff should more focus on what people with schizophrenia want to be in their new life and develop new approaches to enhance rebuilding new goal in life and reduce the self‐stigma.